Skladenjski in pomenski vidiki ekspresivne dvoimenske samostalniške zveze in njene formalne lastnosti v slovenščini - Lipovšek, Frančiška (Jezik in slovstvo, 2025)
The paper presents the type of NP known as an expressive binominal noun phrase (EBNP), which displays the pattern N1-od-N2 in Slovene / N1-of-a-N2 in English, and expresses a subjective evaluation of N2 on the basis of N1 (e.g., that idiot of a driver). The theoretical part discusses the key syntactic and semantic aspects of the structure, drawing upon studies examining its use in English. What makes it special is the following characteristics: absence of the ordinary head-postmodifier relation; N1 and N2 exhibit a predicative relationship (that driver is an idiot); the preposition acts as a linker; N1 represents the syntactic head and N2 the semantic head; N1 mimics an adjective in a relationship with N2 (cf. that idiotic driver); an adjective positioned in front of N1 may semantically modify N1 or N2 (e.g., that reckless idiot of a driver). The empirical part presents a corpus-based analysis of the following formal features of the Slovene EBNP: the use of pronouns and proper names, countability and grammatical number, the types and role of modification. Despite some deviations in comparison with the English EBNP (absence of the article, applicability of pronouns as determiners of N2, acceptability of uncountable nouns as N1 and N2), the patterns of use confirm that the Slovene EBNP accords with the theoretical description of the EBNP proposed by the existing studies.
Keywords: ekspresivna dvoimenska samostalniška zveza; expressive binominal noun phrase; modification; modifikacija; pomensko jedro; semantic head; skladenjsko jedro; Slovene; slovenščina; subjective evaluation; subjektivno vrednotenje; syntactic head